2016
DOI: 10.1007/s12264-015-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Chemokine CXCL12 in the Dorsal Root Ganglia and Spinal Cord Contributes to the Development and Maintenance of Neuropathic Pain Following Spared Nerve Injury in Rats

Abstract: Emerging evidence indicates that CXCL12/ CXCR4 signaling is involved in chronic pain. However, few studies have systemically assessed its role in direct nerve injury-induced neuropathic pain and the underlying mechanism. Here, we determined that spared nerve injury (SNI) increased the expression of CXCL12 and its cognate receptor CXCR4 in lumbar 5 dorsal root ganglia (DRG) neurons and satellite glial cells. SNI also induced longlasting upregulation of CXCL12 and CXCR4 in the ipsilateral L4-5 spinal cord dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 42 publications
6
68
0
Order By: Relevance
“…Increasing evidence supports a role of chemokines in pain control [14]. Xie and co-authors report an active role of the chemokine CCL2 in promoting central sensitization, longterm potentiation, and inflammatory pain [31].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Increasing evidence supports a role of chemokines in pain control [14]. Xie and co-authors report an active role of the chemokine CCL2 in promoting central sensitization, longterm potentiation, and inflammatory pain [31].…”
mentioning
confidence: 98%
“…In the last 5 years, the field has seen tremendous progress in the molecular and functional characterization of primary sensory neurons [6,7], neurocircuits of pain and itch [8][9][10], immune and glial modulation of pain and itch [11][12][13][14][15], molecular mechanisms of pain [16,17], and identification of brain signatures of pain [18]. Thus, it is timely to highlight the recent progress in a second special issue.…”
mentioning
confidence: 99%
“…However, available data about the CXCR4 receptor behavior are contradictory. Whereas some authors, using different models, have demonstrated that CXCR4 activation may promote reversion of cellular damage induced by several insults [6,11,34], other authors have reported the opposite [15,16,17]. In fact, the activation of CXCR4 chemokine receptor led to detrimental effects in these recent studies [14,15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other authors have demonstrated beneficial effects on neuronal function by blocking CXCR4 with AMD3100 [13,16,17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation